2001
DOI: 10.2337/diacare.24.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Epipen as an Alternative to Glucagon in the Treatment of Hypoglycemia in Children With Diabetes

Abstract: OBJECTIVE -Fear of a severe hypoglycemic reaction is a major obstacle to achieving nearnormal plasma glucose levels. Although parenteral glucagon is effective in treating these reactions, it is cumbersome to use, causes severe nausea, and is impractical in the school setting. Epinephrine is available as a premixed injection (Epipen) that may be used by all care providers. Using Epipen to treat hypoglycemia may be an effective, safe, and easy-to-use alternative to glucagon.RESEARCH DESIGN AND METHODS -Ten child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…Adrenaline was commonly used to treat insulin‐induced hypoglycaemia in the first decades of insulin therapy, including in cases of poisoning 24–26 . A small study in children with diabetes made hypoglycaemic by insulin injection found adrenaline injection (300 μg intra‐muscularly) to be ineffective in restoring blood glucose concentration 27 . The β 2 ‐adrenergic agonist terbutaline increased blood glucose concentration in hypoglycaemic experimental subjects with Type 1 diabetes, but not in those with normal insulin secretion, and it was less effective than glucagon 28 …”
Section: Resultsmentioning
confidence: 99%
“…Adrenaline was commonly used to treat insulin‐induced hypoglycaemia in the first decades of insulin therapy, including in cases of poisoning 24–26 . A small study in children with diabetes made hypoglycaemic by insulin injection found adrenaline injection (300 μg intra‐muscularly) to be ineffective in restoring blood glucose concentration 27 . The β 2 ‐adrenergic agonist terbutaline increased blood glucose concentration in hypoglycaemic experimental subjects with Type 1 diabetes, but not in those with normal insulin secretion, and it was less effective than glucagon 28 …”
Section: Resultsmentioning
confidence: 99%
“…This therapy, of course, depends on the patient having adequate glycogen stores. Epinephrine has also been tried in the treatment of hypoglycemia, but was relatively ineffective 31. Amylin, or islet amyloid polypeptide, can also be added to delay gastric emptying resulting in a slower rate of glucose change following a meal, since meals with their rapid rate of change present the greatest challenge to a SQ insulin/SQ sensor closed loop.…”
Section: Pumpsmentioning
confidence: 99%
“…Klinisch werden allerdings immer wieder Bauchschmerzen, Übelkeit und Erbrechen beschrieben (laut Novo-Nordisk in < 1 / 10 000 Fällen), die bei Dosen über 1 mg oder bei rascher Injektion (< 1 Minute) auftreten [10,36,37]. Eigene klinische Erfahrungen bestätigen dies [38], insbesondere eine erhöhte Rate an Erbrechen nach zu schneller Injektion und Erreichen erhöhter Plasmaspiegel durch Hilfspersonen unter Stress [11]. Unklar ist, ob die beschriebenen Nebenwirkungen nur dem Glukagon zuzuschreiben sind oder auch als Symptom der Hypoglykämie gewertet werden kön-nen.…”
Section: Inzidenz Von Hypoglykämienunclassified
“…Glukagon als Notfallmedikation bei Hypoglykä-mie sollte bereits in jedem T1DM-Haushalt vorhanden sein. Es ist bislang als "letzte" Möglichkeit in hoher Dosierung mit Nebenwirkungen, insbesondere Erbrechen, behaftet [11]. Die niedrig dosierte Glukagongabe könnte unter Berücksichtigung der spezifischen Indikation und ergänzend zu den bisherigen Therapiemaßnahmen nebenwirkungsarm helfen, wiederholt niedrige Werte bei hypoglykämischen Episoden im Rahmen von Infekten zu behandeln [38 -40, 42].…”
Section: Tab 2 üBersicht üBer Veröffentlichungen Zur Niedrig Dosiertunclassified
See 1 more Smart Citation